2018
DOI: 10.1016/j.avsg.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stent Shows Similar Patency Results as Prosthetic Bypass in Patients with Femoropopliteal Occlusion in a Randomized Trial

Abstract: The trial was preregistered at ClinicalTrials.org (NCT01450722).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The mean lesion length of 264 mm was higher than in any comparable trial with values ranging from 132 to 241 mm. 79 Other studies only report 2-year results (primary patency: 56%-70%, freedom from TLR: 70%–86%), including the use of drug-coated balloons, novel NS and heparin-bonded stent grafts, which were comparable to our results (primary patency:48%; freedom from TLR:73%; at 2 years). The higher lesion length in our stent group may have impaired secondary patency at 2 years with only 64% compared to those studies with 80% to 98%.…”
Section: Discussionsupporting
confidence: 84%
“…The mean lesion length of 264 mm was higher than in any comparable trial with values ranging from 132 to 241 mm. 79 Other studies only report 2-year results (primary patency: 56%-70%, freedom from TLR: 70%–86%), including the use of drug-coated balloons, novel NS and heparin-bonded stent grafts, which were comparable to our results (primary patency:48%; freedom from TLR:73%; at 2 years). The higher lesion length in our stent group may have impaired secondary patency at 2 years with only 64% compared to those studies with 80% to 98%.…”
Section: Discussionsupporting
confidence: 84%
“…Our search identified 57 eligible RCTs from 69 articles enrolling a total of 9,362 patients comparing seven revascularization strategies (balloon angioplasty vs. bare metal stent vs. covered stent vs. paclitaxel eluting stent vs. other drug eluting stent vs. paclitaxel‐coated balloon vs. bypass surgery; Figure 1). 1,2,16‐82 Other drug eluting stents category included sirolimus/zotarolimus/everolimus eluting stent. Cochrane risk of bias is summarized in Figure S2a, b. Baseline characteristics are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Patency rates between the groups did not differ significantly after 12 and 24 months. 20 In these studies, the primary patency rate after 12 months for endovascular therapy was 63% to 65% and 64% to 67% after bypass surgery. Furthermore, secondary patency for both endovascular therapy and bypass surgery after 1 and 2 years was lower (72% to 86%) 18,20 than the 97% secondary patency in the current study after 3 years.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, several studies with different endovascular approaches showed equivalent outcomes after endovascular therapy vs bypass surgery. 1820 A study comparing BMS to vein bypass in long femoropopliteal lesions (mean lesion length 276 mm) showed no significant differences between groups regarding patency, limb salvage, survival, or complications after 24 months. 18 After 1 year, the SuperB study, 19 which compared heparin-bonded endoluminal bypass with femoropopliteal bypass (two-thirds being venous bypass grafts), revealed promising results after endovascular therapy with lower morbidity, faster recovery, and improvement in quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation